Bioelectrochemical profiling of two common polymorphic variants of human FMO3 in presence of graphene oxide. (20th February 2017) - Castrignanò, Silvia; Bortolussi, Stefania; Catucci, Gianluca; Gholami, Omkolsum; Valetti, Francesca; Gilardi, Gianfranco; Sadeghi, Sheila J.
Graphical abstract: Abstract: Genetic variation of phase I drug metabolising enzymes has been shown to greatly influence inter-individual reaction to pharmacological treatments. Among these enzymes, human flavin-containing monooxygenase 3 (hFMO3) plays a crucial role and understanding its pharmacogenetics is fundamental for the prediction of individual drug response and the efficacy of therapy. In this work the altered drug metabolism of two common polymorphic variants of hFMO3 (E158K and E308G) are studied by using an electrochemical platform modified with graphene oxide (GO). Electrochemistry was used to characterise the properties of these two engineered and purified hFMO3 variants followed by electrocatalysis experiments in the presence of three different hFMO3 substrates benzydamine, tamoxifen and sulindac sulfide. HPLC quantification of the electrochemically produced metabolites showed that E158K mutation leads to an impairment of N-oxygenation activity while E308G mutation enhances the same activity. Results demonstrate that electrocatalysis on GO modified glassy carbon electrodes provides a fast and reliable method for measuring kinetic parameters of hFMO3 polymorphic variants. This method can be considered suitable for deciphering metabolic implications of polymorphisms that might lead to adjustment of drug dosages depending on the individual's genetic makeup, a step closer to the development of personalised medicine.